INTERPRETATION OF RELIGIOUS FIGURES TOWARD WALI ADHOL ACCORDING TO ISLAMIC LAW AND THE MARRIAGE LAW (Case Study in Kec.Aek Nabara Barumun Kab, Padang Lawas) - Habibullah habib (Universitas Dharmawangsa, 2023)
In this case the author looks at the interpretation of religious leaders towards Adhol wali according to Islamic law and the Marriage Law whose legal sources refer to the Fatwa of the Indonesian Ulama Council, towards the interpretation of religious figures towards this adol's wali. not inferring from generalizations. This study also uses a comparative approach. Research sources were also obtained from religious leaders and interviews with religious leaders and walis who were reluctant to marry off their daughters and included sources from the perpetrators of elopement as well as Ulama (MUI) of Aek Nabara Barumun District, and secondary data obtained from literature books, journals, articles, and other literature which serve as references or complementary sources for research. This study concludes that the interpretation of religious figures towards Adol walis according to Islamic law and the Marriage Law should be that the views of religious figures can be taken and guided for the benefit of the ummah and society and society must also comply with the marriage law to protect and maintain human dignity as creatures. the most perfect according to Law No. 1 of 1974 which is perfected by Law No. 16 of 2019 concerning marriage, then all citizens who enter into marriage must submit and comply with the marriage law in force in Indonesia.